Effect of crystallization on enhancement of mechanical property for polylactide-b-polyisoprene-b-polylactide triblock copolymers. (12th August 2020) - Ding, Shuangshuang; Fang, Chu; Zhang, Juan; Wang, Xuehui; Wang, Zhigang
Abstract: We have reported a mild synthesis of triblock copolymers, polylactide- block -polyisoprene- block -polylactide (termed as PLA- b -PI- b -PLA), which are environment-friendly sustainable elastomers. In this paper, the thermal stability, viscoelastic property and mechanical property for these triblock copolymers are investigated due to their application purpose and the effect of formation of PLA crystals on their mechanical property is particularly concerned with because the end blocks of these triblock copolymers are crystallizable when prepared by solvent-casting after their synthesis. Dynamic thermomechanical analysis discloses two separate glass transitions associated with sufficiently high storage moduli due to their typical phase-separated morphology with the glass transition temperature of hard glassy phase domains higher than ambient temperature. Wide-angle X-ray diffraction technique (WAXD) demonstrates that the end blocks crystallize and eventually PLA α -form crystals form. The variable mechanical property of triblock copolymers can be obviously enhanced by controlling crystallization of the end blocks, with the crystallized PLA domains replacing the glassy amorphous PLA domains, facilitating development of sustainable green elastomers with sufficient applicable mechanical property. Graphical abstract: Image 1 Highlights: The mechanical property of PLA- b -PI- b -PLA triblock copolymers is obviously enhanced by crystallization of the PLA blocks. Sufficient thermal stability for broad applications is confirmed for PLA- b -PI- b -PLA triblock copolymers. PLA phase domains become stronger when PLA crystals replace the amorphous glassy PLA.